Effect of various boundary constraints on the collapse behavior of multi-story composite frames. (15th July 2022) - Tan, Zheng; Zhong, Wei-hui; Meng, Bao; Zheng, Yu-hui; Duan, Shi-chao
Abstract: Previous studies on the influence of boundary constraints on the structural collapse behavior have primarily focused on single-story sub-assemblages, and the limited research on multi-story frames is insufficient to accurately reflect the actual boundary constraints of each story. As these boundary constraints exert a significant influence on the internal force redistribution and development of load resistance mechanisms, this study proposes numerical simulation models to elucidate the influence of various boundary constraints on the collapse behavior of multi-story composite frames. First, the high-fidelity modeling methods were validated by comparison with previous experimental results. Subsequently, the existing boundary constraint problems of previous collapse studies were highlighted, and the collapse behaviors of two models with either elastic or actual boundary constraints were compared. The results indicated that the elastic boundary constraints, which were widely used in previous collapse studies, overestimated the later resistance of multi-story composite frames compared with that of actual boundary constraints. Thus, the boundary constraint equation for each story was conservatively proposed when evaluating the collapse resistance of multi-story frames, considering the post-buckling behavior of peripheral columns. Subsequently, the validated model was employed to study the influence of different boundary constraints (column-removal position and number of beam spans) on the collapse behavior described by the load–displacement response, axial force development, horizontal deformation characteristics, and load resistance mechanisms. Furthermore, the resistance contribution coefficients were quantitatively evaluated to provide a reference for structural design engineers. The results indicated that the resistance provided by the first and second stories decreased with the outward movement of the failed-column position, whereas that by the third story increased. In addition, the flexural mechanism resistance and resistance provided by the first story decreased with increasing boundary constraints, whereas the catenary mechanism resistance and the resistances provided by the second and third stories increased. Moreover, the resistance contributions of each story tended to be consistent with the other stories. Highlights: The existing problems on boundary constraints in the existing collapse studies were proposed. Good agreement between the simulation and experimental results was observed. Collapse behavior under elastic and actual boundary constraints was compared. The post-buckling behavior of peripheral columns was considered. The effects of column-removal position and number of beam spans were investigated.